LIFE LONG LEARNING PROCESS TO REFORM THE THEORIES AND PRACTICES OF EDUCATION SECTOR IN THE COUNTRY - Poghosyan , G. S.; Gasparyan, A.M.; Amiryan, E.V. (Modern Psychology, 2022)
This article analyzes the theoretical foundations of lifelong learning as opportunities for a person to live and flourish in a democratic society. Continuous learning, according to the existing concept, implies that a person needs to constantly keep learning, update the acquired knowledge, skills and abilities. It should be implemented throughout life not only by means of natural communication, life experience, but also through the realization of variety conscious educational opportunities via formal, non- form and informal education. In the article, determinations, standards and objectives of the lifelong learning listed in local and international literature are stated. Detailed analysis of the authors’ work, models and reports, as well as the approaches of different specialists of our country are set out.Video-methodological analysis shows that almost all European countries, including China, are shifting from adult to continuing education, and then to lifelong learning.
Keywords: lifelong education; lifelong learning; continuing education; formal; non-form and informal education